Conceptual Engineering and Conceptual Ethics - Burgess, Alexis; Cappelen, Herman; Plunkett, David (Oxford University Press, 2020)
Conceptual engineering is a branch of philosophy that is concerned with assessing representational devices such as concepts and words. Conceptual engineers looks for the problems with such devices and attempt to come up with ways of improving flawed concepts: they attempt to say how those concepts should be. This is the first volume devoted entirely to the possibility, benefits, problems, and applications of conceptual engineering and conceptual ethics. It consists of twenty chapters; some advocate for the field, while others develop sceptical arguments, and some focus on the various methodological issues that arise while others apply the method to issues in metaphysics, epistemology, ethics, and social and political philosophy.